Peningkatan Kemampuan Bahasa Inggris Siswa Kelas VIII SMP N I Sampaga - Susiandari, Ariawati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
English has become an important skill in the era of globalization which increasingly demands cross-border communication competence. Mastery of English opens up wider opportunities, both in the world of education, career and in international relations. The aim of this PkM is to improve the English language skills of students at SMP Negeri 1 Sampaga, especially in class VIII. This program will focus on providing interactive training, using technology and interesting learning media, as well as holding additional classes oriented towards developing practical English language skills. The PkM method is that participants are given motivation, understanding, elaboration (discussion and question and answer), games, dialogue and practice, the resource person conducts a question and answer session. The results show that there is an increase in the average score of the pre-test and post-test, that the result of the pre-test score is 43 and the result of the post-test score is 67. The conclusion is that there is a significant difference in the results before and after the learning activities. Therefore, the activity to improve English language skills, especially grammar, in class VIII students of SMPN I Sampaga, Sampaga District, Mamuju District was declared successful based on evidence from the results of this activity.